How to target vascular leakage in retinopathy: could a lipid tighten the pipes? - M Luisa Iruela‐Arispe (EMBO Molecular Medicine)
Abstract Retinopathy is one of the more severe complications associated with diabetes. Targeting vascular pathology has shown benefits, but current therapies are costly and have limitations. In this issue of EMBO Molecular Medicine, Niaudet et al report that the activation of the S1PR1 receptor in endothelial cells is able to block abnormal permeability, neovascular tuft development, and resolve pathological vascular lesions associated with hypoxia‐driven retinopathy.